KONSER DIDI KEMPOT SEBAGAI BENTUK SOSIALITAS BARU DI ERA LATE MODERNITY - Rahma Novita (Journal of Development and Social Change, 2021)
This article try to explain the experiences of the young people of Sobat Ambyar in watching the Didi Kempot concert which formed a new form of sociality in the era of late modernity. Specifically, in this study there were four informants who were randomly selected by the researcher with certain criteria. In this study using a qualitative method with a phenomenological approach. The data obtained were based on in-depth interviews with informants. This study shows that there is one form of sociality in the era late modernity, although it is only temporary, not binding with membership that keeps changing. Besides that, the experience of watching a Didi Kempot concert is one of the coherent self-narratives to show that the sociality of neo-tribes can interact with reflexive individualism. Key note : Sobat Ambyar, Neo-tribes, Youth, Didi Kempot